NATURE LOST: IMPACTS AND RESTORATION STRATEGIES FOR EARLY CHILDHOOD IN THE DIGITAL AGE - Surinchompoo, Chatwilai; Wattananan, Achara; Boonprakorn, Kawin (Journal of Education and Innovation, 2025)
The exploration of the impact of the digital age on early childhood, particularly the lack of nature, which may lead to developmental issues, has shown through the study of fundamental principles, concepts, and various research, the great importance of nature in the learning and development process of young children. The disappearance of nature in the current era is attributed to parents, guardians, and educational institutions placing excessive importance on the use of digital technology. This has led to an imbalance in daily activities, which rely heavily on digital technology at all times. Therefore, there is a need for collaboration to address, support, and develop the impact and methods of restoration for young children in the digital age. This involves balancing their lives with a conscious use of digital technology and integrating restorative methods that emphasize free play and learning from nature, to holistically strengthen the development of young children in the digital age.